PENGARUH HARGA JASA PELAY ANAN KEBERSIHAN( CHARGING FOR SER VICE) TERHADAP RENT ABILIT AS PD. KEBERSIHAN KOTA BANDUNG - Gilang Rieza Puspita, - (2008)
Perusahaan daerah Kebersihan Kota Bandung (PD. Kebersihan) is one of BUMD which is estabilished by Bandung sub-province local government. One of the mision PD. Kebersihan is receive earning. But in fact, It didn't has ability to find the earning at operational activities.It is supported by lost which is realized in every years. ABSTRAC Rentability is the right instrument for measure financial performance at PD. Kebersihan. It is usually comparison between earning and total assets. When earning getting more, this condition can give good contribution for increasing the rentability, so with the financial performance too. The effort of PD. Kebersihan to get earning is increasing the number of fund resources which is comes from cleanness charging for service. It is very potential for balance the operational cost. The result of research in which conducted at PD. Kebersihan with analyse data and get the result of Cleanness Charging for Service as X variable and Rentability as Y variable and then processed by statistic test of Rank Spearman Correlation, indicates that Cleanness Charging for Service give influence for rentability of PD. Kebersihan Kota Bandung.